USM PLANS TO OFFER ACADEMIC PROGRAMMES WITH TUT JAPAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 29 May 2015 An international cooperation between Universiti Sains Malaysia (USM) and Toyohashi University of Technology (TUT) Japan would provide more capacity in enhancing existing collaborations while exploring new programmes. The ViceChancellor of USM, Professor Dato’ Dr. Omar Osman said, USM and TUT would widen the scope of the various cooperation in academic programmes and research, especially in the areas of Material Sciences and Electronics Engineering.